Speaking in Gestures: left dorsal and ventral frontotemporal brain‐systems underlie communication in conducting - Musso, Mariacristina; Altenmüller, Eckart; Reisert, Marco; Hosp, Jonas Aurel; Schwarzwald, Ralf; Blank, Bettina; Horn, Julian; Glauche, Volkmar; Kaller, Christoph; Weiller, Cornelius; Schumacher, Martin (2023)
Abstract: Conducting constitutes a well-structured system of signs anticipating information concerning the rhythm and dynamic of a musical piece. Conductors communicate the musical tempo to the orchestra, unifying the individual instrumental voices to form an expressive musical Gestalt. In a functional magnetic resonance imaging (fMRI) experiment, 12 professional conductors and 16 instrumentalists conducted real-time novel pieces with diverse complexity in orchestration and rhythm. For control, participants either listened to the stimuli or performed beat patterns, setting the time of a metronome or complex rhythms played by a drum. Activation of the left superior temporal gyrus (STG), supplementary and premotor cortex and Broca's pars opercularis (F3op) was shared in both musician groups and separated conducting from the other conditions. Compared to instrumentalists, conductors activated Broca's pars triangularis (F3tri) and the STG, which differentiated conducting from time beating and reflected the increase in complexity during conducting. In comparison to conductors, instrumentalists activated F3op and F3tri when distinguishing complex rhythm processing from simple rhythm processing. Fibre selection from a normative human connectome database, constructed using a global tractography approach, showed that the F3op and STG are connected via the arcuate fasciculus, whereas the F3tri and STG are connected via the extreme capsule. Like language, the anatomical framework characterising conducting gestures is located in the left dorsal system centred on F3op. This system reflected the sensorimotor mapping for structuring gestures to musical tempo. The ventral system centred on F3Tri may reflect the art of conductors to set this musical tempo to the individual orchestra's voices in a global, holistic way